2021
DOI: 10.2147/dmso.s306433
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Serum Vitamin B12 and Folate Levels and Macrocytosis in Patients with Type 2 Diabetes Mellitus on Metformin Attending Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia: A Cross-Sectional Study

Abstract: Background Metformin is the first-line drug in the treatment of type 2 diabetes mellitus. Monitoring vitamin B 12 deficiency associated with long-term and high-dose therapy is not a common practice in many clinical settings in Ethiopia. Objective The study aimed to measure levels of serum vitamin B 12 and folate and to assess the macrocytic status of type 2 diabetes mellitus patients on metformin. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
0
1
Order By: Relevance
“…The results of examining the mean age variable in patients showed that the mean age in patients with a normal range of vitamin B12 and patients with vitamin deficiency is higher compared to other studies. So that in the study of W Wale Tesega et al (2021) (28). The mean age of the patients was 56 years, which is lower than the mean age of the present study.…”
Section: Discussioncontrasting
confidence: 66%
“…The results of examining the mean age variable in patients showed that the mean age in patients with a normal range of vitamin B12 and patients with vitamin deficiency is higher compared to other studies. So that in the study of W Wale Tesega et al (2021) (28). The mean age of the patients was 56 years, which is lower than the mean age of the present study.…”
Section: Discussioncontrasting
confidence: 66%